PEMANFAATAN APLIKASI ANBUSO DALAM PENILAIAN HASIL BELAJAR DI SD NEGERI SUKAMAJU BARU 1 DEPOK - Heriyati Heriyati; *Munasiah Munasiah; Zikriah Zikriah (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2023)
Learning Outcomes Assessment is the process of collecting information or data about students' learning achievements in the attitude aspect, knowledge aspect and skill aspect carried out by educators in a planned and systematic manner to monitor the process, learning progress, and improvements and efforts to improve learning outcomes. The importance of assessing learning outcomes is to monitor learning progress, monitor learning outcomes, and detect the need to improve learning outcomes from students on an ongoing basis. Educators, especially formal school teachers, need applications to facilitate the processing and assessment of learning outcomes. One application that can be used to process scores is the Question Item analysis application known as AnBuSo. This activity was carried out in December 2022, attended by 10 teachers and school principals. This activity has been able to increase teachers' knowledge about assessing learning outcomes by utilizing the AnBuso application